Sicily 2024 - Steves, Rick, 1955- (Rick Steves' guidebook series. City, regional and country guides., 2024)
"Swim in the sparkling Mediterranean, marvel at the peak of Mount Etna, and get to know this region's timeless charm: with Rick Steves on your side, Sicily can be yours!"--Publisher.